2008
DOI: 10.1016/j.tripleo.2008.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Gender- and age-based differences in computerized tomographic measurements of the orophaynx

Abstract: Objective-To examine the influence of aging and body-mass-index (BMI) on the oropharynx configuration in male and female Japanese patients.Study design-This study examined the computed tomography (CT) images of 19 male and 19 females, group matched for age and BMI. The airway and the soft tissue volumes between the posterior nasal spine and top of the epiglottis were compared.Results-The patient's height, total oropharynx length (TOL), and lower oropharynx lengths and volume measurements (soft tissue and airwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 20 publications
(21 reference statements)
4
34
0
7
Order By: Relevance
“…The total height of the oropharynx and the volume of this segment demonstrated a statistically significant difference between genders (larger in men). Among the study participants, the changes increased with age, and age was a significant predictor of the oropharynx length 29,30 .…”
Section: Discussionmentioning
confidence: 92%
“…The total height of the oropharynx and the volume of this segment demonstrated a statistically significant difference between genders (larger in men). Among the study participants, the changes increased with age, and age was a significant predictor of the oropharynx length 29,30 .…”
Section: Discussionmentioning
confidence: 92%
“…Johnston and Richardson [22] repeated cephalometric radiographs measurements of 16 adults after 32 years, and showed that the vertical oropharynx length increased by 4.7 mm after 20 years of age. Yuko et al [13] found that, in OSA male and female patients, pharyngeal airway length significantly correlated with age after being adjusted for height, and the lengthening with age was greater in men than in women. The findings above indicated that the difference in pharyngeal airway length between sexes appears since puberty, and airway length changes throughout adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…The findings above indicated that the difference in pharyngeal airway length between sexes appears since puberty, and airway length changes throughout adulthood. Longer airway increases the pharyngeal collapse potential [13,25,28], and this difference in airway anatomy may be a risk factor of high male-tofemale ratio for OSA.…”
Section: Discussionmentioning
confidence: 99%
“…The limits of the oropharyngeal (OP) volume were defined on the midsagittal slice, anteriorly by the incisive canal and the midline of the upper incisors. 20 The superior border of the OP volume was defined by the palatal plane (ANS-PNS) line extending to the posterior wall of the pharynx, and the inferior border was defined by the line passing from the most inferoanterior point on the body of the third cervical vertebra and the base of the epiglottis ( Figure 2). In addition to volumetric measurements, the surface area of the most constricted area between the previously mentioned limits was recorded in relation to the occlusal plane as above the occlusal plane (AOP), below the occlusal plane (BOP), or on the occlusal plane (OccP).…”
Section: Methodsmentioning
confidence: 99%